Disentangling fiscal effects of local constitutions - Monika Köppl-Turyna; Jarosław Kantorowicz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We apply the difference-in-discontinuities design to disentangle the fiscal effects the governance system conditional on electoral systems. We take advantage of a natural experiment, which involves two institutional reforms in Poland. Our results indicate that a change from parliamentary to presidential form led to lower vertical fiscal imbalance predominantly in the jurisdictions with majoritarian elections and to a lesser extent in municipalities governed by proportional elections.
Keywords: D72; D78; H72; 330